Numerical simulation and experimental study on the characteristics of armature wear and contact process of small caliber railgun - Huayi Zhang; Benfeng Gu; Baoming Li; Chunxia Yang (Defence Technology)
During the electromagnetic railgun launch process, high temperature and high current conditions can lead to armature wear, affecting armature/rail contact and degrading launch performance. This paper starts with the analysis of the metal liquid film formation at the armature/rail contact interface. 1D and 3D models are developed based on the characteristic relational equation obtained from the melt liquid film model. These models incorporate thermodynamic equilibrium phase diagram, transient heat and mass transfer model, copper-aluminum alloy reaction model, nonlinear electrical conductivity relational equation and nonlinear thermal conductivity relational equation to analyze the temperature distribution and copper-aluminum intermetallic compounds (Cu-Al IMCs) formation in the melt liquid film. The wear mechanism and influence law of armature are explained in detail from different perspectives to understand and predict the transition and gouging phenomena at the contact interface. The model's validity is confirmed by the results of electromagnetic launch experiments, providing insights for future structure design and material selection of the armature and rail.